Instrument Response Standard in Time-Resolved Fluorescence Spectroscopy at Visible Wavelength: Quenched Fluorescein Sodium. Issue 5 (May 2014) - Liu, Mengwei; Jia, Menghui; Pan, Haifeng; Li, Lei; Chang, Mengfang; Ren, Hua; Argoul, Françoise; Zhang, Sanjun; Xu, Jianhua
Time-resolved fluorescence properties of quenched fluorescein sodium, including self-quenching and collisional quenching by iodide, have been studied by using a picosecond time-correlated single-photon counting (TCSPC) apparatus, together with an upconversion spectrophotofluorometer with a time resolution better than 300 fs. The steady-state fluorescence intensity of fluorescein sodium reached the maximum when its concentration was 510 μM with pH > 9. Both the fluorescence intensity and lifetime decreased with increasing concentrations of NaI quencher. When the NaI concentration was 12.2 M, a monoexponential decay with a lifetime as short as 17 ps was exactly determined for the first time using the femtosecond-resolved upconversion system. Picosecond time-resolved fluorescence measurements of circular permuted green and yellow fluorescent proteins (cpGFP and cpYFP) were reported, demonstrating that the fluorescence decay of quenched fluorescein sodium is a better approximation of the instrument response function (IRF) needed for the accurate deconvolution of fluorescence lifetime data, particularly for detectors used in the visible spectral region. We believe that this picosecond lifetime standard will find wide applications in fluorescence lifetime imaging microscopy (FLIM).